Exploring the participant experience in controlled human infection model (CHIM) trials: A modified grounded theory study - Anna G. Mack; Donna M. Halperin; Bailey M. Selig; Brian R. Condran; Scott A. Halperin (PLoS ONE, 2025)
Background Controlled human infection model (CHIM) trials are useful tools for accelerating vaccine development through the deliberate infection of healthy volunteers in a controlled environment to study the course of disease in humans. CHIM trials may pose physical, psychological, and social harms to participants. Participants are subjected to long inpatient stays and daily sample collection, which may be uncomfortable. Very little is known about the CHIM trial participant experience and decision-making process. Methods We conducted a modified grounded theory study, embedded within the Canadian Center for Vaccinology (CCfV)’s Bordetella pertussis CHIM trial. Twenty six participants engaged in semi-structured interviews at four time periods throughout their year-long involvement in the CHIM trial, using a constant comparative approach of simultaneous data collection and analysis. This process continued until saturation was reached and an emerging theoretical model was constructed depicting the CHIM trial participant experience over time. Results The emergent conceptual model centered around the core category “A Trusting Partnership”, depicting the evolution of the participant-researcher relationship throughout the experience. Establishing trust was critical during the decision-making phase, facilitated through transparent researcher-participant communication and consideration of past experiences and values. Supporting the trusting partnership during the inpatient isolation phase was facilitated through ongoing researcher-participant engagement and emotional support. During outpatient participation, maintaining the trusting partnership was achieved through effective communication, consistent follow-up care, and recognition of participants’ contributions. Quality improvement (QI) recommendations were identified across all phases of CHIM trial participation. Conclusions Researcher-participant trust is an integral component of the CHIM trial participant experience. QI recommendations should be taken into consideration when planning and coordinating future CHIM trials.